Synthesis of a cyclic tetramer of 3-amino-3-deoxyallose with axially oriented amino groups. (January 2022) - Yudina, Olga N.; Gening, Marina L.; Talukdar, Pinaki; Gerbst, Alexey G.; Tsvetkov, Yury E.; Nifantiev, Nikolay E.
Abstract: A linear tetramer of β-(1 → 6)-linked 3-azido-3-deoxy-d -allose containing glycosyl donor and glycosyl acceptor functions in the terminal monosaccharide units was prepared starting from 3-azido-3-deoxy-1, 2:5, 6-di- O -isopropylidene-α-d -allofuranose. Cyclization of the linear tetramer under glycosylation conditions afforded the corresponding cyclic tetrasaccharide in 77% yield; its deprotection and reduction of the azido groups resulted in the formation of the cyclic tetramer of 3-amino-3-deoxy-d -allose with axial amino groups, a potential scaffold for the synthesis of tetravalent functional clusters. Graphical abstract: Image 1 Highlights: Linear tetramer of β-(1→ 6)-linked 3-azido-3-deoxy-d -allose was prepared Cyclization of the linear precursor afforded the cyclic tetramer of 3-azido-3-deoxy-d -allose. Processing of the cyclic tetraazide produced the cycle with four axial amino groups. The tetramine is a potential scaffold for the synthesis of tetravalent functional clusters.